Property investment decision-making behaviour amidst market disruptions: an institutional perspective. Issue 1 (12th August 2020) - Bolomope, Muhammed; Amidu, Abdul-Rasheed; Filippova, Olga; Levy, Deborah
Abstract : Purpose: Decision-making behaviour of property investors has been the focus of real estate research for decades. Yet, there is no consensus on a generally accepted behavioural model that suits all market conditions and investment peculiarities. While scholars have emphasized the significance of rational reasoning and cognitive influences on property investment decision-making preferences, gaps remain regarding the impacts of market disruptions on property investment decision-making behaviour. This paper, therefore, explores the institutional framework as a theoretical basis for understanding property investment decision-making behaviour amidst market disruptions. Design/methodology/approach: This paper reports a systematic review of pertinent theories that have explored decision-making behaviour. Commencing with an index search of high impact peer-reviewed journals, a snowball identification of relevant citations was also deployed to assemble theories from the field of psychology, sociology, economics and urban studies. Although a preliminary dataset of 82 papers with relevant decision-making theories was identified, the final dataset comprised 27 papers and 7 theories. The identified theories were reviewed accordingly. Findings: The outcome of this study suggests that the institutional framework offers a robust approach to property investment decision-making amidst market disruptions, especially because it recognizes the dynamism in the investment environment and the roles of formal and informal rules that exist therein. Originality/value: This study advances the current understanding of property investment decision-making behaviour by recognising the dynamism of the investment environment and how factors such as principles, laws, tradition and routines can lead to an established and legitimate standard of reasoning. By integrating both rational and cognitive attributes, the study provides a holistic perspective to property investors' decision-making behaviour in response to market disruptions.